Transnacional The Offense of Criminal Association in Argentine law Considering the Requirements of the United Nations Convention against Transnational Organized Crime - Santiago Cordini, Nicolás (2024)
This article examines organized crime from a conceptual perspective, aiming to determine its existence and clarify its nature. The central hypothesis suggests that Argentina, like other countries, experiences delays in fulfilling international obligations, continuing to operate with previous concepts. The research uses a qualitative methodology, employing a comparative content analysis. The first section reviews the normative foundations established by the United Nations Convention against Transnational Organized Crime (UNTOC), emphasizing its role in shaping global policies. Subsequently, the Argentine legal framework is analyzed, focusing on the crime of " criminal association," and compared with the UNTOC's definitions and principles. This analysis reveals both congruences and divergences in the conceptualization of organized crime. Additionally, the proposed Anti-Mafia Law in Argentina is examined, evaluating its potential effectiveness in strengthening the legal framework to combat organized crime. The results highlight Argentina's efforts to adopt a more politically efficient concept than “criminal association," aligning with international standards.